2021
DOI: 10.1021/jacs.1c07780
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of N-CF3 Alkynamides and Derivatives Enabled by Ni-Catalyzed Alkynylation of N-CF3 Carbamoyl Fluorides

Abstract: The expansion of chemical space associated with ubiquitous motifs is key to unleash new properties and functions. In this context, alkynamides, prevalent in numerous drugs and materials, represent an untapped resource. We herein report the first synthetic access to N-trifluoromethyl alkynamides. Our strategy relies on a mild and operationally simple Ni-catalyzed coupling of N-CF 3 carbamoyl fluorides with alkynyl silanes. The synthesized N-CF 3 alkynamides proved to be highly robust and readily functioned as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…Alkynamides are common motifs in many drug molecules. Schoenebeck and co-workers reported facile access to N -trifluoromethyl alkynamides via Ni-catalyzed coupling of N -CF 3 carbamoyl fluorides with alkynyl silanes . The resulting N -CF 3 alkynamides were demonstrated to be easily functionalized to access synthetically challenging derivatives such as N -CF 3 -derived alkenyl amides, quinolones, or oxindoles (Scheme ).…”
Section: Recent Reports On Ni-catalyzed Reactionsmentioning
confidence: 99%
“…Alkynamides are common motifs in many drug molecules. Schoenebeck and co-workers reported facile access to N -trifluoromethyl alkynamides via Ni-catalyzed coupling of N -CF 3 carbamoyl fluorides with alkynyl silanes . The resulting N -CF 3 alkynamides were demonstrated to be easily functionalized to access synthetically challenging derivatives such as N -CF 3 -derived alkenyl amides, quinolones, or oxindoles (Scheme ).…”
Section: Recent Reports On Ni-catalyzed Reactionsmentioning
confidence: 99%
“…Recently, Schoenebeck et al ingeniously designed a nickel-catalyzed cross-coupling of N-CF 3 carbamoyl fluorides with alkynylsilanes to overcome existing limitations, given the importance of N-CF 3 amide compounds in pharmaceutical engineering and the total synthesis of natural products (Scheme 11). 36 This reaction protocol realized the selective C-F bond activation of carbamoyl fluorides by a commercially available nickel catalyst under mild conditions in order to couple with alkynylsilanes while retaining the N-CF 3 amide bonds. The introduction of a C-C triple bond into the molecule gives the products as key synthons, and further derivatization can be used to build a series of N-CF 3 alkenylamides, oxindoles, and quinolones that were previously synthetically inaccessible.…”
Section: Scheme 10 Nickel-catalyzed Intramolecular Cyclization and Ar...mentioning
confidence: 99%
“…However, recent reports have demonstrated that carbamoyl fluorides are competent electrophiles in crosscoupling reactions, while also offering unique reactivity compared to their chlorinated counterparts. 10,11 Thus, developing more efficient methods for their preparation is an ongoing pursuit. 12−22 Carbamoyl fluorides are commonly accessed from the carbamoyl chloride via halogen exchange with an inorganic metal fluoride salt, which is typically used in large excess.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In comparison to carbamoyl chlorides, the use of carbamoyl fluorides in organic synthesis remains largely underdeveloped. , This observation could be related to the limitations associated with their synthesis and/or reduced electrophilicity. However, recent reports have demonstrated that carbamoyl fluorides are competent electrophiles in cross-coupling reactions, while also offering unique reactivity compared to their chlorinated counterparts. , Thus, developing more efficient methods for their preparation is an ongoing pursuit. …”
Section: Introductionmentioning
confidence: 99%